Pengaruh Likuiditas, Laverage, dan Komisaris Independen Terhadap Efective Tax Rate (Studi Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Purwanti, Desi; Ruliani, Ruliani; Novita, Intan (Department of Accounting, Faculty of Economics & Business, 2022)
Effective tax rate is one way for companies to avoid taxes by comparing the tax burden with total net income. This study aims to examine and analyze the effect of liquidity, leverage, and independent commissioners on the effective tax rate. This study is quantitative research by applying secondary data, namely financial statements. The population consists of mining corporations listed on the Indonesian Stock Exchange for the period 2015-2019. The sample is determined using a teleological sampling method and then generated 70 data observations or 14 companies over a five-year research period. The technique for analyzing data through multiple linear regression. The results demonstrated that liquidity affected the effective tax rate, that leverage did not affect the effective tax rate, and that independent commissioners did not affect the effective tax rate.